2014
DOI: 10.1089/jwh.2013.4397
|View full text |Cite
|
Sign up to set email alerts
|

Individual, Provider, and System Risk Factors for Breast and Cervical Cancer Screening Among Underserved Black, Latina, and Arab Women

Abstract: Characteristics associated with breast and cervical screening adherence differs among Black, Latina, and Arab underserved women. Interventions to improve screening should be tailored for racial/ethnic groups with particular attention to competing survival priorities, health literacy risks factors, and provider recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 42 publications
3
56
0
Order By: Relevance
“…Moreover, women’s desire for more traditional print media in health education suggests that existing outreach materials may not be reaching their intended targets. These findings support the ongoing need for community-based health education and interventions that are appropriately tailored for underserved women (Roman et al, 2014; Russell, Monahan, Wagle, & Champion, 2007). …”
Section: Discussionsupporting
confidence: 68%
“…Moreover, women’s desire for more traditional print media in health education suggests that existing outreach materials may not be reaching their intended targets. These findings support the ongoing need for community-based health education and interventions that are appropriately tailored for underserved women (Roman et al, 2014; Russell, Monahan, Wagle, & Champion, 2007). …”
Section: Discussionsupporting
confidence: 68%
“…Roman, Meghea, Ford, et al (2014) confirmed the sentiments of the women in this community that competing priorities and responsibilities to others often take precedence and force personal care to come second or third to these overriding issues. Study During the discussion groups women described fear and motivation as mediating factors that influenced health-seeking behaviors.…”
Section: Explanation For Behaviors Of Late-diagnoses and Non-adherencesupporting
confidence: 59%
“…Roman et al’s study of non-HIV infected, underserved Black, Latina and Arab women in Dearborn, Michigan found that cervical cancer screening in Black women was lower among those reporting higher scores for “competing priorities,” a score indicating working two jobs, having low household income, and needing to reschedule multiple appointments [37]. Improving communication in the patient-clinician relationship can increase engagement in HIV care, improving HIV-related health overall [38].…”
Section: Resultsmentioning
confidence: 99%